Vindication of linking social capital capacity to urban agriculture: a paradigm of participation based on social empowerment in Klang Valley, Malaysia - Nazuri, Nur Shuhamin; Rosnon, Mohd Roslan; Ahmad, Nobaya; Ahmad Suhaimi, Siti Shazwani; Sharifuddin, Juwaidah; Wijekoon, Rusitha (MDPI AG, 2022)
With the rise of urbanization, the Malaysian government faces a tough challenge in ensuring food and nutrition security, especially for the disadvantaged urban populations. Urban agriculture (UA) seems to be a feasible approach to be undertaken by the government to overcome urban food insecurity. In distinguishing UA as a vital element of sustainable urban development, the primary challenge is to develop effective programs that engage urban dwellers and organizations through good design and implementation. Additionally, empowering communities through UA programs is challenging. Hence, the major aim of this study is to ascertain the assigned and underlying values of UA participation amongst communities that contribute to aspects of community social empowerment in Klang Valley, Malaysia. The dataset for the study was taken from the respondents (180) who were the participants of UA community programs authorized by the Department of Agriculture in Klang Valley area, and a Structural Equation Modelling using Partial Least Square (PLS-SEM) was utilized to integrate the interdependencies between multiple variables. The findings revealed the important role of participation in the planning, implementation, and evaluation of UA programs to ensure success. Participation should be seen through the roles of agencies, NGOs, and communities in order to build a strong network crucial to the enhancement of social empowerment among participants of UA programs.